PERMINTAAN JAGUNG SEBAGAI BAHAN BAKU INDUSTRI PAKAN TERNAK DI INDONESIA - Diah Ariyanti; Any Suryantini; Masyhuri Masyhuri (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2008)
The objectives of this research are to know the factors influencingdomestic maize demand, import maize demand, and total maize demand asraw material for feed industry in Indonesia, also their trend at five yearslater. The research use time series data. during 1976-2004. Simultaneousequations used to analyze domestic and import maize demand as rawmaterial for feed industry in Indonesia, while ordinary least square (OLS)used to analyze total maize demand as raw material for feed industry inIndonesia. The results show that domestic maize demand influenced negatively by maize domestic price and influenced positively by soybean cake import price, and trend of time. Cowpopulation, maize import price, and soybean cake import price influence import maize demand negatively, while fowl population and trend of time influence import maize demand positively. Total maize demand for feed industry in Indonesia positively influenced by soybean cake import price and cow population, and negatively influenced by maize domestic price. Soybean cake iscomplementary good for domestic maize and total maize, but becomesubstitution good for import maize. The trend of maize demand, includingdomestic and import maize demand, as raw material for feed industry inIndonesia increasing in the future.